SIKAP BAHASA GURU SEKOLAH DASAR TERHADAP BAHASA INDONESIA RAGAM TULIS BAKU - Wijayanti, Sri Hapsari; Darmoyo, Syarief; Dhian, Yohanna Claudia (Jurnal Pendidikan Bahasa dan Sastra, 2018)
The fostering of positive attitude toward Indonesian language to the students is done at least by teachers who also have a positive attitude towards the Indonesian language. This study aimed to observe the language attitude of elementary school teachers in Jakarta towards Indonesian formal writing and to reveal whether there are differences in language attitudes in terms of the status of schools (private and public). This study is descriptive qualitative and quantitative. Data collected through essay writing tests, questionnaires, and interviews. Questionnaires were distributed to 57 respondents from five areas in Jakarta, while the interviews were conducted to 12 teachers. Likert scales questionnaire form consist of statements about three components of attitude, namely cognitive, affective, and conative. This study found that elementary school teachers in Jakarta has a positive attitude towards Indonesian formal writing. Additionally, there were no significant differences between the language attitudes of public school teachers and private school teacher of elementary school. Although this study found that the teachers have a positive attitude towards Indonesian formal writing, their writing still showed deficiencies in application of aspects of language.Â